Re-Considering the Origins of the Climate Emergency: War, Finance, and the State - Tim Di Muzio; Matt Dow (London Journal of Research in Humanities and Social Sciences, 2023)
One of the most important and recurring debates in the field of International Political Economy and international affairs are the links between capitalism, fossil fuel energy and climate change. In these debates, the origins of our current climate emergency are rooted in how Britain became the first country to become reliant on mass production and consumption coal (fossil fuels) for economic growth, industrialization, as well as social reproduction. Britain becoming a coal-fire capitalist-imperial global empire deeply influenced and structured the current world order and global political economy which is still locked-into a vicious cycle of path dependency whereby balance of power, production and social reproduction is dependent on energy, predominately fossil fuels.
Keywords: H56; Q5; Q54; P18; O14; B51; P1; 330; capital; climate; crisis; energy; finance; industrialization; Marxism; power; state; war